Analysis of modified sitting positions for subarachnoid block: A prospective observational study - Nousheen Chowdhary; Ajaiz Rasool; Raja Suhail Shounthoo; Majid Jehangir; Rohey Jan; Showkat Ahmad Gurcoo (Asian Journal of Medical Sciences, 2025)
Background: Neuraxial block is one of the most common anesthetic modalities for a wide range of surgical procedures. Conventionally, it is mostly performed in classical sitting position (CSP), however, a few modifications of sitting position have been described in literature since patient positioning is by far the most crucial factor for a successful subarachnoid block (SAB). Proper positioning of the patients reduces lumbar lordosis and facilitates easy palpation of the landmarks. Aims and Objectives: Comparison of three different sitting positions including classical sitting position (CSP), hamstring stretch position (HSP), and riders sitting position (RSP), for SAB. Materials and Methods: A total of 207 patients, divided equally into three groups (CSP, HSP and RSP) with 69 patients in each group. Spinal anesthesia was given in three different sitting positions, and the parameters were recorded with respect to time taken for intrathecal placement of the needle, number of punctures, ease of palpation of space, patient comfort, and anesthesiologists’ satisfaction. Results: Confirmation of subarachnoid placement of needle required the least time in RSP group (P=0.003), majority of patients in RSP required a single skin puncture (P=0.0237), clarity of the bony landmarks was similar in all the three positions (P=0.108), patients’ satisfaction score was highest in CSP group (P=0.012); however, anesthesiologists’ reported higher satisfaction levels in RSP group, although results were statistically non-significant (P=0.739). Conclusion: From the anesthetist’s standpoint, RSP was the most favorable position for spinal anesthesia, however, the majority of patients reported better comfort levels with CSP.